Comparative analysis of glucose-6-phosphate dehydrogenase levels in pre-term and term babies delivered at University of Ilorin Teaching Hospital, Nigeria - Temitope Olorunsola Obasa; Omotayo Olukemi Adesiyun; Olugbenga Ayodeji Mokuolu; Ayodele Isaac Ojuawo (MDPI AG, 2012)
Glucose-6-phosphate (G6P) is an enzyme in the hexose monophosphate shunt required for the production of reducing equivalents needed to mop up free radicals. thereby keeping hemoglobin in its free state. Deficiency of the enzyme can cause severe neonatal jaundice. The aim of this study was to compare G6PD levels in pre-term and term babies, and evaluate the extent to which G6PD deficiency determines the severity of jaundice in various gestational age groups. Samples of cord blood collected from consecutively delivered babies in the University of Ilorin Teaching Hospital, Nigeria, were assayed for G6PD levels, and the babies were observed for jaundice during the first week of life. Those who developed jaundice had serial serum bilirubin measured. Nine hundred and thirty-three babies had G6PD assayed, with 348 being G6PD deficient, giving a hospital based prevalence of 37.3%. Of the 644 who were followed up, 143 (22.2%) were pre-term and 501(77.8%) were term babies. Babies with gestational age (GA) 27-29 weeks had the highest G6PD levels. However, there was no significant variation among the different gestational age groups (F=0.64, P=0.64). Jaundice occurred more in pre-term compared to term babies with a relative risk of 2.41 (χ2=60.95, P=0.00001). Occurrence of jaundice in pre-term babies was irrespective of G6PD status (χ2=0.2, P=0.66, RR=1.09, CI=0.83